Outbreak of carbapenem-resistant Acinetobacter baumannii in the intensive care unit: a multi-level strategic management approach. Issue 2 (February 2016) - Molter, G.; Seifert, H.; Mandraka, F.; Kasper, G.; Weidmann, B.; Hornei, B.; Öhler, M.; Schwimmbeck, P.; Kröschel, P.; Higgins, P.G.; Reuter, S.
Summary: An outbreak of carbapenem-resistant Acinetobacter baumannii (CRAb) occurred in an interdisciplinary intensive care unit, affecting 10 patients. Within hours of recognition of the spread of CRAb an intervention team was instituted for collection of available data, decision-making, communication and monitoring of all interventions performed, including cohorting, temporary stop of admissions, staff education, and enforcement of infection control measures. An area was defined for cohortation of patients colonized with CRAb, with a separate nursing team and a second set of mobile equipment. New transmissions were no longer observed after only four days into the institution of enhanced infection control measures.